Giant Ekstra Bintaro Membangun Kesadaran Merek Produk UMKM Melalui Strategi Komunikasi Pemasaran Terpadu - Prahara Gunadi, Taufan (Communication, 2019)
Giant Ekstra Bintaro is committed to developing local products by accepting and marketing UMKM products in various outlets that are widespread in many cities in Indonesia. Because all this time marketing has become a plan for small and medium entrepreneurs in developing businesses. What is done by Giant Extra Bintaro is conducting promotional activities in building brand awareness or approving brands in consumers' memories for UMKM products, with the aim of determining one product with another product or competitive product. With high brand awareness, Giant Extra Bintaro to increase sales of UMKM food products specifically for fresh and snack categories. This study aims to determine a series of marketing activities carried out by Giant Extra Bintaro for UMKM products. The method of analysis used qualitative description independent interview to several informants inside the company and of course to the customer itself. Based on result of analysis, it can be concluded that Giant Ekstra binatro sektor 7 Tangerang Selatan has applied Integrated Marketing Communication for their marketing activity and also treat UMKM’s product same like the regular one. However, because of the limited funds the UMKM’s suppliers can not fully participate to the marketing activities. Finnaly unaware brand has resuited because the customers prefer to buy daily needs product in the cheaper or discount prices without knowing wether it’s the UMKM product or not.